POLA KOLABORASI BISNIS CV. PROMINDO UTAMA (Studi Kasus di Desa Losari Lor, Kecamatan Losari Kabupaten Cirebon) - Hafizah Putri Ramadhani; Iwan Setiawan (Universitas Galuh Ciamis, 2021)
Collaboration is a process of thinking in which the parties involved look at the different aspects of a problem and find solutions to these differences and their limited views on what can be done. Collaboration is defined as togetherness, cooperation, sharing of tasks, equality, and responsibility where the collaborating parties have the same goal, common perception, willingness to process, and provide mutual benefits. This research is motivated by the fact that the process, mechanism and benefits of collaboration between CV. Promindo Utama and its partners do not always go as desired. This condition can certainly hinder the development of the company and or correct the company to make improvements in collaboration patterns in partnerships. In general, this study aims to determine how the business collaboration patterns built by CV. Promindo Utama with its partners and know the factors that support and tend to hinder the collaboration. This research uses descriptive qualitative research. The data collection used was observation and interviews which were conducted for about 1 month. The results showed that in general the collaboration between CV. Promindo Utama and its partners have been running optimally even though there are still some obstacles. Besides the obstacles that exist, the collaboration pattern that occurs is able to run smoothly.